Nontraumatic Laryngeal Fractures: Report of Two Cases and Review of the Literature - Alfredo Santamaría; Ricardo Alarcón; Ilson Sepúlveda; Felipe Fredes (Case Reports in Otolaryngology)
Laryngeal fractures occur mainly in the context of cervical trauma, hanging, or strangulation. Nontraumatic laryngeal fractures are rare and there are few reports in the literature. We present two cases of nontraumatic laryngeal fractures evaluated in our service.